Technology in the ancient world - Hodges, Henry (Barnes & Noble, Inc, 1992)
1. Intro : how we know what we do about preliterate and early literate cultures and their environment 2. From savage hunter to primitive farmer : the new skills and tools essential to stock raising and agriculture 3. The spread of farming and the emergence of embryonic cities and of writing 4. Of monuments, ships, metallurgy and military technology 5. Of chariots, sea-going ships and the expansion of trade 6. Of Greeks and roads and riding horses 7. The late Greek and Roman engineers and their devotion to machinery 8. The barbarians of Northern Europe, India, China and the New World ; Bibliographical Note, Index